2022
DOI: 10.1177/10556656221138895
|View full text |Cite
|
Sign up to set email alerts
|

Does Distraction Lower Risk of VPI Compared to Conventional Maxillary Advancement? A Retrospective Cohort Study of Adolescents with Cleft Palate

Abstract: Objective To determine whether method of maxillary advancement in adolescents with cleft palate with or without cleft lip (CP ± L) influences post-operative velopharyngeal function. Design Retrospective cohort. Setting Pediatric Tertiary Care Hospital. Participants One hundred and ninety-nine patients with CP ± L after LeFort I osteotomy for maxillary advancement at our institution between January 2007 and June 2019. Interventions LeFort I osteotomy via distraction osteogenesis (DO) or conventional osteotomy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 46 publications
0
2
0
2
Order By: Relevance
“…This is particularly relevant, given that recent studies have noted that small quantitative differences (<1 mm) have been reported to influence velopharyngeal function, and these differences may be correlated with the perception of hypernasality. 56,57 For example, in patients that demonstrate velopharyngeal insufficiency, use of the curvilinear measurement provides more accurate quantitative assessment of the velar morphology and likelihood for postoperative VP function, particularly as it relates to distraction osteogenesis 30 and obstructive sleep apnea. 58 Furthermore, functional differences may also be observed when assessing velar length during phonation due to patient-specific anatomy postpalatoplasty, again highlighting the need to precisely measure this structure using a curvilinear measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant, given that recent studies have noted that small quantitative differences (<1 mm) have been reported to influence velopharyngeal function, and these differences may be correlated with the perception of hypernasality. 56,57 For example, in patients that demonstrate velopharyngeal insufficiency, use of the curvilinear measurement provides more accurate quantitative assessment of the velar morphology and likelihood for postoperative VP function, particularly as it relates to distraction osteogenesis 30 and obstructive sleep apnea. 58 Furthermore, functional differences may also be observed when assessing velar length during phonation due to patient-specific anatomy postpalatoplasty, again highlighting the need to precisely measure this structure using a curvilinear measurement.…”
Section: Discussionmentioning
confidence: 99%
“…6,10,17,20,[27][28][29] Thus, the VP needs ratio has been supportive as an anatomic indicator for the ability to achieve VP closure during speech. 12,13,23,[30][31][32] Notably, within these seminal works, a measure of linear velar length is often described and measured as a straight line from the posterior maxillary point (PMP) or posterior nasal spine (PNS) to the uvular tip. This is common in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…A repercussão da cirurgia ortognática com avanço de maxila sobre a função velofaríngea de indivíduos com fissura labiopalatina tem sido objeto de estudo nos últimos anos. A literatura já demonstrou que a deterioração dessa função não está diretamente relacionada à quantidade de avanço maxilar 4,12,13 . Atualmente, os estudos estão sendo direcionados na busca pela identificação dos fatores preditivos do aparecimento e/ou agravamento da disfunção velofaríngea após a cirurgia ortognática.…”
Section: Discussionunclassified
“…No entanto, não houve correlação entre o aparecimento da disfunção velofaríngea e a quantidade de avanço maxilar, constatando-se que a piora da função velofaríngea foi mais evidente nos casos em que o palato mole apresentava menor extensão. Mais recentemente, Kinter et al (2022) 13 mostraram que pacientes que realizaram o avanço de maxila por meio de distração osteogênica apresentaram maiores escores de hipernasalidade em relação aos tratados com avanço de maxila convencional.…”
Section: Discussionunclassified